2019
DOI: 10.1177/2516043519838176
|View full text |Cite
|
Sign up to set email alerts
|

Second victims and mindfulness: A systematic review

Abstract: Second victims are healthcare professionals who have been involved in an unanticipated clinical event or medical error and are negatively impacted on professional and/or personal levels. One of the most prevalent symptoms second victims endure is stress, which correlates with burnout and powerlessness. These symptoms may deeply impact second victims on professional and personal levels, but can also influence healthcare organizations. Distracted and stressed clinicians can possibly create a medical error and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…• Support from managers at all levels, counselors or therapist, department/unit or institution and psychological support (6,9,15,29,33,(43)(44)55,59,61,(65)(66)68,70,(75)(76) • Website Mitigating Impact in Second Victims (MISE) (39,(42)(43)(50)(51) • Second Victim Support Unit (USVIC) (62) • Coping strategies (13,16,(23)(24)(25)30,35,44,46,61,(63)(64) • Support from co-workers, spouse, family members, friends and multidisciplinary team ( 6,13,16,30,42,44,58,61,66,77) • Training and learning from error (24,42,(67)(68)71,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Support from managers at all levels, counselors or therapist, department/unit or institution and psychological support (6,9,15,29,33,(43)(44)55,59,61,(65)(66)68,70,(75)(76) • Website Mitigating Impact in Second Victims (MISE) (39,(42)(43)(50)(51) • Second Victim Support Unit (USVIC) (62) • Coping strategies (13,16,(23)(24)(25)30,35,44,46,61,(63)(64) • Support from co-workers, spouse, family members, friends and multidisciplinary team ( 6,13,16,30,42,44,58,61,66,77) • Training and learning from error (24,42,(67)(68)71,…”
Section: Resultsmentioning
confidence: 99%
“…Another aspect of this category was the conception that some studies addressed interventions and actions based on strategies with an emphasis on the problem and on emotion/cognition (35,(42)(43)61,63) and coping strategies, among them reflective writing (7,25) , temporary leave from work (33,55) , selfpunishment, self-defense or fact denial (27,35,55,63,66,71) and depersonalization (55) . Learning with error (42,(67)(68)71,(75)(76) , positive feedback (24,42) , proactive education (74) and the participation of the second victim in the AE root cause analysis process, in the construction of action plans and in the validation of the decision-making process to avoid future incidents (71,76) were also mentioned as a source of support for training.…”
Section: Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Miller et al review the literature on the effectiveness of mindfulness-based interventions -a distinctly nontechnical solution -to reduce stress, burnout, and increase self-compassion in healthcare workers who have become second victims. 14 Adams et al analyzed a large database to investigate how healthcare systems handled patient safety events related to Health Information Technology. 15 They found that nearly two-thirds of events had not been resolved at the time of reporting.…”
mentioning
confidence: 99%
“…review the literature on the effectiveness of mindfulness-based interventions – a distinctly non-technical solution – to reduce stress, burnout, and increase self-compassion in healthcare workers who have become second victims. 14…”
mentioning
confidence: 99%